Multimodality Imaging in the Diagnosis of Prosthetic Valve Endocarditis: A Brief Review - Eder, Maxwell D.; Upadhyaya, Krishna; Park, Jakob; Ringer, Matthew; Malinis, Maricar; Young, Bryan D.; Sugeng, Lissa; Hur, David J. (Frontiers in Cardiovascular Medicine, 2021)
Infective endocarditis is a common and treatable condition that carries a high mortality rate. Currently the workup of infective endocarditis relies on the integration of clinical, microbiological and echocardiographic data through the use of the modified Duke criteria (MDC). However, in cases of prosthetic valve endocarditis (PVE) echocardiography can be normal or non-diagnostic in a high proportion of cases leading to decreased sensitivity for the MDC. Evolving multimodality imaging techniques including leukocyte scintigraphy (white blood cell imaging), 18F-fluoro-dexyglucose positron emission tomography (FDG PET), multidetector computed tomographic angiography (MDCTA), and cardiac magnetic resonance imaging (CMRI) may each augment the standard workup of prosthetic valve endocarditis and increase diagnostic accuracy. While further studies are necessary to clarify the ideal role for each of these imaging techniques, nevertheless, these modalities hold promise in determining the diagnosis, prognosis, and care of prosthetic valve endocarditis. We start by presenting a clinical vignette, then evidence supporting various modality strategies, balanced by limitations, and review of formal guidelines, when available. The article ends with the authors’ summary of future directions and case conclusion.